КАЧЕСТВО ЖИЗНИ И МИКРОБИОЦЕНОЗ КИШЕЧНИКА БОЛЬНЫХ РЕВМАТОИДНЫМ АРТРИТОМ - М. Ю. Гульнева; С. М. Носков; Т. С. Носкова; Э. В. Малафеева (Архивъ внутренней медицины, 2014)
A study of quality of life in patients with rheumatoid arthritis development of varying degrees of violations of the microflora of the large intestine and found that the development of disorders of the intestinal microflora is accompanied by a significant change in the quality of life of patients. In patients with varying degrees of violations of microbial gut microbiota observed decline in physical and psychological components of health. The lowest values of quality of life in patients fitted with the II degree of microbiological violations microbiota of the large intestine.